A rare case of recurrent Guillain Barre Syndrome. (Indian Journal of Child Health, 2019)
After the reduction of poliomyelitis, Guillain–Barre syndrome (GBS) has become the most common cause of acute flaccid paralysis in the developed and developing countries. Although it is a monophasic illness, GBS might reoccur in 1–6% of patients, after an asymptomatic period of several months to years. Risk factors for recurrent GBS (RGBS) include age less than 30, milder symptoms, and history of Miller-Fisher syndrome variant in the first episode. A recurrence was defined as two or more episodes that fulfilled the National Institute of Neurological and Communicative Disorders and Stroke criteria for GBS, with a minimum time between episodes of 2 months (when fully recovered in between) or 4 months (when only partially recovered). There appears to be no significant difference between GBS and RGBS episodes with respect to clinical symptoms and triggering events. We report a 12-year-old girl who presented with a second attack of GBS after an interval of 6 years with similar signs and symptoms. Nerve conduction study in both the episodes was of acute motor axonal neuropathy variety.